Culturally relevant social work services for latinas infected or affected with HIV/AIDS. - Rodriguez Escobar, Yolanda; Pomeroy, Elizabeth C.; Holleran, Lori K.; Noel, LaTonya (Facultad de Trabajo Social y Desarrollo Humano, 2004)
As we begin the third decade of the HIV/AIDS pandemic, concerns continue about social, psychological, and behavioral aspects of the living with the illness. What was once thought to be predominately a gay, Anglo disease has now become prominent in the heterosexual population crossing all racial and class lines. Presumed injection drug users have always been highly infected. However, studies show that HIV/AIDS is affecting different populations at shockingly disproportionate rates. The HIV/AIDS pandemic in the United States is disproportionately represented and is growing at a faster rate in ethnic minority communities as compared to majority populations (Centers for Disease Control and Prevention [CDC], 2002). The purpose of this article is to explore the specific issues associated with HIV/AIDS in racial and ethnic minorities, with a specific focus on how the increase of new AIDS cases is affecting Latinas. Disparities such as lack of access to medical care and unique socio-cultural issues are discussed, followed by implications for social work practice, policy, research, and education.